Família homoafetiva sergipana : o tribunal de justiça de Sergipe e o novo conceito de família - Falcão, Valquiria Nathali Cavalcante (2018)
The purpose of this study is to analyze the jurisprudence formed by the Court of Justice of the State of Sergipe regarding civil homoeffective judgments within the family between 2005 and 2015, seeking to draw a profile of the local judiciary in refers to the grounds of decisions rendered in the second degree of jurisdiction. As a starting point will be made a preliminary study on the theory of the State and how the judiciary gained strength in post-liberalism, which came to settle with the establishment of Constitutional States, with Brazil included in this. Subsequently, on the stabilization of the judiciary power, the concepts and theories on judicialization of judicial politics and activism will be analyzed, and how the aforementioned phenomena have contributed to the formation of a new right of Brazilian families, especially those formed by same sex. In the end, the research will present whether the Sergipe judiciary, in the grounds of its decisions to recognize the rights of this new family formation, has been activist or not.